A Computer-Based Method to Improve the Spelling of a Learner with Dyslexia (Journal of Social Sciences Review, 2023)
For students, academic writing is a must skill to be honed to achieve good grades from teachers and majority novice learners commit errors in spellings. Such students with spelling errors lag behind other peers. In this paper we present a method which aims to improve the spelling of children with dyslexia through playful and targeted exercises. Manual correction of spelling errors involves a person manually checking and correcting misspelled words. Auto correction is faster and more efficient than manual correction, but it may also introduce new errors and may not always be accurate. This case study aimed to investigate the   influence   of   word-office   as   a tool on spelling improvement and accuracy as while writing in word-office misspelled word is highlighted and student can correct spelling.  For this purpose, we  conducted research on one student  Grade 8 with  spelling  difficulties  in  a  special school  for  special  needs  to  participate in  writing essays. This research took the form of writing manually on a paper and typing another essay with the use of word-office software. The study concludes that there is reasonable amelioration in student’s achievement in correction of spellings with the use of typing spelling. Furthermore, this research has implications for the development of new technology and software designed to support learners with dyslexia.
Keywords: A Case Study; Corrections; Errors; Word-office; Writing; Dyslexia; Learner